Penyimpanan Protokol Notaris Dengan Konsep Elektronik Dengan Cyber Notary - Rosa, Meilina (Magister Kenotariatan, Universitas Jambi, 2024)
The purpose of this study is to understand and analyze the urgency of electronic storage of notarial protocols within the concept of cyber notary. Additionally, it aims to explore the regulations and procedures for electronic storage of notarial protocols in Indonesia and South Korea. The electronic storage of notarial protocols, as envisioned by this concept, has not yet allowed for the transition to electronic media; notaries are still required to maintain conventional storage methods. Consistent with the legal research method used, which is normative juridical research. This involves reviewing the applicable laws and regulations and utilizing secondary data as the primary data source. Based on the research findings, it can be concluded that the ambiguity in the existing norms necessitates significant improvements and evaluations related to the regulation of electronic storage of notarial protocols, which may be feasible to implement in Indonesia, provided it does not conflict with existing laws and continues to fulfill the authenticity requirements of deeds as stipulated in Article 1868 of the Indonesian Civil Code (KUHPerdata)